Design and evaluation of mRNA encoding recombinant neutralizing antibodies for botulinum neurotoxin type B intoxication prophylaxis - Gulisaina Qiaerxie; Yujia Jiang; Gege Li; Zhixin Yang; Feng Long; Yunzhou Yu; Jian Sheng Lu; Peng Du; Yong Cui (Taylor & Francis Group, 2024)
Among all natural and synthetic toxins, botulinum neurotoxins (BoNTs), produced by Clostridium botulinum in an anaerobic environment, are the most toxic polymer proteins. Currently, the most effective modalities for botulism prevention and treatment are vaccination and antitoxin use, respectively. However, these modalities are associated with long response time for active immunization, side effects, and donor limitations. As such, the development of more promising botulism prevention and treatment modalities is warranted. Here, we designed an mRNA encoding B9-hFc - a heavy-chain antibody fused to VHH and human Fc that can neutralize BoNT serotype B (BoNT/B) effectively - and assessed its expression in vitro and in vivo. The results confirmed that our mRNA demonstrates good expression in vitro and in vivo. Moreover, a single mRNA lipid nanoparticle injection effectively prevents BoNT/B intoxication in vivo, with effects comparable to those of protein antibodies. In conclusion, we explored and clarified whether mRNA drugs encoding neutralizing antibodies prevent BoNT/B intoxication. Our results provide an efficient strategy for further research on the prevention and treatment of intoxication by botulinum toxin.